2012
DOI: 10.1111/j.1463-1318.2011.02921.x
|View full text |Cite
|
Sign up to set email alerts
|

Short‐term results for laparoscopic ventral rectopexy using biological mesh for pelvic organ prolapse

Abstract: In the short term, LVR using biological mesh is safe and as effective as synthetic mesh, with high patient satisfaction. Constipation and faecal incontinence scores were both improved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
48
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(48 citation statements)
references
References 19 publications
(26 reference statements)
0
48
0
Order By: Relevance
“…Looking at studies using the same technique, but with biologic instead of synthetic mesh, improvement rates can reach 95 % for constipation and for incontinence, although it must be noted that these results are observed with shortterm follow-up [9,10].…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Looking at studies using the same technique, but with biologic instead of synthetic mesh, improvement rates can reach 95 % for constipation and for incontinence, although it must be noted that these results are observed with shortterm follow-up [9,10].…”
Section: Discussionmentioning
confidence: 88%
“…However, these did show 82-95 % improvement of obstructed defaecation syndrome (ODS) symptoms and 73-95 % improvement of FI [9,10]. The lack of comparative data does not allow us to establish the superiority of any biologic mesh in terms of surgical complications, as well as short-and longer-term functional outcomes [11].…”
Section: Introductionmentioning
confidence: 85%
“…the data interpreted within this study, therefore, include patients who have been reported previously by the individual centers. [3][4][5][8][9][10][11][12][13][14][15][16][17] the indication for patients undergoing lVR was at the discretion of individual center practice. however, 4 of the 5 centers included within this study were involved in the creation of a published consensus for lVR with standardized indications for surgery, 18 and, as such, practice was consistent among all of the centers.…”
Section: Methodsmentioning
confidence: 99%
“…However number of biological meshes used are small and the long-term efficacy of biological materials in pelvic floor repair has yet to be defined [8,9]. The increased cost of the bio prosthetics is also of concern [10][11][12][13]. Long-term evidence and well-powered randomized trials are needed to fully define the roles of the various meshes in ventral mesh rectopexy.…”
Section: Discussionmentioning
confidence: 99%